Antioxidant and Membrane Stabilizing Activities of Bark of Sonneratia apetala (Bangladesh Pharmaceutical Journal, 2016)
This study was carried out to investigate the antioxidant activity in terms of free radical scavenging capacity and membrane stabilizing ability of methanol extract of bark of Sonneratia apetala. The total phenol content of the extract was measured by Folin-Ciocalteu reagent. The antioxidant potential was investigated using 2,2 diphenylpicrylhydrazyl (DPPH), reducing power assay and chelating power determination. The membrane stabilizing capacity was assessed by monitoring the hypotonic solution - and heat-induced haemolysis of human erythrocytes. The total phenolic content was found 50.75 mg/gm of gallic acid equivalent. The extract exhibited significant antioxidant activity in DPPH free radical scavenging assay with IC50 value of 81.42 µg/ml as compared to the standard, BHT (IC50=42.56 µg/ml), Fe2+ ion reducing power assay and chelating power ability. In case of assay for chelating ability, EDTA represented 98.76% chelation while the plant extract showed 82.83% at concentration of 100 ?g/ml. In addition, the methanol extract of bark of this plant was found to moderately inhibit the haemolysis of human erythrocyte. In conclusion, the methanol extract of S. apetala could be valuable candidate for future development for antioxidant activity.Bangladesh Pharmaceutical Journal 19(2): 147-151, 2016